Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1088/0957-4484/22/34/345102
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of atomic force microscopy-based cell elasticity measurements

Abstract: Atomic force microscopy (AFM) is widely used for measuring the elasticity of living cells yielding values ranging from 100 Pa to 100 kPa, much larger than those obtained using bead-tracking microrheology or micropipette aspiration (100-500 Pa). AFM elasticity measurements appear dependent on tip geometry with pyramidal tips yielding elasticities 2-3 fold larger than spherical tips, an effect generally attributed to the larger contact area of spherical tips. In AFM elasticity measurements, experimental force-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
154
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(168 citation statements)
references
References 26 publications
13
154
1
Order By: Relevance
“…In our simulations of cell indentation, the endothelial cell is modeled as a nearly incompressible (14,27) hyperelastic neo-Hookean (13,28,29) material, with a Poisson's ratio of 0.49 and a Young's modulus of 1 kPa. The microindenter's spherical tip is considered infinitely rigid compared to the cell.…”
Section: Simulations Of Cell Indentationmentioning
confidence: 99%
“…In our simulations of cell indentation, the endothelial cell is modeled as a nearly incompressible (14,27) hyperelastic neo-Hookean (13,28,29) material, with a Poisson's ratio of 0.49 and a Young's modulus of 1 kPa. The microindenter's spherical tip is considered infinitely rigid compared to the cell.…”
Section: Simulations Of Cell Indentationmentioning
confidence: 99%
“…40 Moreover, it has been demonstrated that it is possible to detect length and grafting density of the brush layer on living cells, 65,66 or even to distinguish between cancerous and healthy cells' brushes, 67 thanks to the sensitivity of micrometric spherical probes provided by their wider surface area.…”
Section: Colloidal Spherical Probesmentioning
confidence: 99%
“…The first factor is the AFM probe, such as tip shape and spring constant of cantilever. Harris and Charras [71] used both standard conical cantilevers and the same cantilevers modified with a spherical tip to measure cell Young's modulus, showing that Young's modulus measured by conical tips was 2-3 fold larger than that measured by spherical tips. Vargas-Pinto et al [72] have also shown that the Young's modulus of human umbilical vein endothelial cells (HUVEC) and Schlemm's canal (SC) endothelial cells measured by spherical tips (0.71 ± 0.16 kPa and 0.94 ± 0.06 kPa) was significantly smaller than that measured by conical tips (3.23±0.54 kPa and 6.67±1.07 kPa).…”
Section: E Factors Influencing Afm Mechanical Measurementsmentioning
confidence: 99%